Characterization of the volatile compounds in tea (Camellia sinensis L.) flowers during blooming - Guo, Xiangyang; Wang, Lulu; Huang, Xiuting; Zhou, Qiying (Frontiers in Nutrition, 2025)
Tea flower, with characteristic flavor formed during blooming, are a significant tea resource. However, studies on the volatile compounds of tea flower and their aroma characteristics during flowering are scarce. In this study, the odor characteristics of tea flower during blooming were comprehensively investigated by GC–MS, PCA, ACI determination and sensory evaluation. The tea flower of unopened buds (TF-S1) contained the highest alcohol amounts, while fully opened tea flowers (TF-S3) had the highest heterocyclic compounds. Half-opened tea flowers (TF-S2) had the most volatile compounds, including high levels of linalool and its oxides, and low levels of (Z)-3-hexen-1-ol. Acetoin and cosmene were first identified in TF-S1 and TF-S2, respectively. The major ACI components differed, with linalool being prominent exhibiting ACI above 27 in all samples. Acetophenone, unique to TF-S2 with ACI of 57.35, contributed to sweet odor. Furthermore, PCA analysis and sensory evaluation revealed distinct aroma characteristics among the samples. Overall, TF-S2 and TF-S3 had higher volatile amounts and better aroma properties with floral, powdery or almond-like odors. These results advance the understanding of aroma properties of tea flower during blooming, and provide a reference for resource utilization and promotion of the application in food or cosmetics industries.